Coronavirus and the Colonisation of Private Life. Issue 1 (March 2021) - Thornton, Margaret
Abstract : The idea of a distinction between public and private life has a long history in political thought, but the boundary between them has become increasingly blurred as a result of temporal flexibility. Technological change lies at the heart of the ability to choose when and where work is performed, including 'working at home'. This refers only to productive work so that the unpaid domestic and caring work that women disproportionately undertake has been excluded. Its invisibility has led to it 'counting for nothing' in the computation of the Gross National Product. With particular regard to the gender ramifications of working at home, this article analyses the responses to an on-line survey conducted in Australia when lockdown was a key prong of the government response to COVID-19 in 2020. As unpaid work was integrated with productive work, it is suggested that the rationale for discounting it in national accounts no longer holds, especially as the sphere of intimacy is insidiously being colonised by capitalism.